La doble vulnerabilidad de la mujer embarazada privada de la libertad y la afectación de sus derechos en el centro de privación de la libertad de personas adultas en conflicto con la ley de Riobamba - Betty Carolina, Mena Salazar (2019)
The Constitution of Ecuador of 2008, brought substantial changes, one of them is the consecration of more favorable rights for the benefit of people belonging to priority care groups, among which are pregnant women and people deprived of liberty, in addition The Constitution in its article 35 refers that those persons who are or are part of two or more of these priority groups, because of this condition, will be in a situation of double vulnerability and in this regard the State will give greater attention and prioritize their rights and guarantee. Thus, there is a situation in the administration of justice, when judging women, there are occasions that are in a state of gestation or in turn become pregnant while serving their sentence, thus becoming in a situation of double vulnerability since they seriously affect their rights, when serving their sanction in a detention center. As in the present investigation, a study of the rights of persons and priority attention groups will be carried out regarding pregnant women and persons deprived of liberty, in order to analyze the problem of the double vulnerability of that group of people, through the analysis of cases, the study of a ruling of the Constitutional Court, and finally being able to determine what are the legal mechanisms applicable in cases in which pregnant women have been deprived of liberty.